Evaluating biosecure entry and exit protocols and education methods in a mock livestock facility - Schuft, Abby; Noll, Sally; Janni, Kevin; Hetchler, Brian; Martinson, Krishona; Cortus, Erin (Frontiers in Veterinary Science, 2026)
IntroductionTeaching biosecure protocols to farm workers and visitors is essential to maintaining healthy herds and flocks in animal agriculture. Our study objective was to evaluate the effects of protocols with varying steps, education methods, and short and mid-term retention on the number of errors and time to complete entry and exit processes in a mock livestock facility.MethodsUniversity participants were recruited to learn and demonstrate biosecure protocols. Three simulated farm entryways were constructed with a unique set of protocols assigned (Protocol) to each entryway. Using common industry practices, Protocol 1 established three core procedures: signing a logbook, removal of outerwear and personal items, and management of a phone or other device. Protocols 2 and 3 used the same core procedures with 3 and 4 additional steps, respectively. The additional steps included changing footwear, crossing a line of separation, using hand sanitizer, donning barn-specific clothing (Protocol 3 only). Participants learned procedures via one of three educational modalities (Method): listen, read, or watch. Short-term retention was assessed as participants completed all three protocols in forward (Entry) and reverse order (Exit) starting from a randomly assigned initial protocol (Initial). When half of the participants returned after a lapse of time (>1 month; Round), they had to rely on their recall of the procedures. Mixed-effects linear regression was used to model entry and exit time (Time), and a Poisson regression was used to model the entry and exit errors (Errors) committed.ResultsAnalysis showed education Method did not influence Errors or Time during Entry or Exit. Participants made 1.37 times more Entry Errors (P ≤ 0.02) and 1.19 times more Exit Errors (P ≤ 0.17) during round 2 compared to round 1. Compared to Protocol 1, participants made 1.47 times more Errors on average during Protocol 2 (P ≤ 0.02) and 1.87 times more during Protocol 3 (P ≤ 0.001). The time to complete the entry procedures was associated with Protocol, Round and the Initial experience, but exit time was only associated with Protocol and Round.